Inefficient DNA repair is an aging-related modifier of parkinson's disease (2016)
The underlying relation between Parkinson's disease (PD) etiopathology and its major risk factor, aging, is largely unknown. In light of the causative link between genome stability and aging, we investigate a possible nexus between DNA damage accumulation, aging, and PD by assessing aging-related DNA repair pathways in laboratory animal models and humans. We demonstrate that dermal fibroblasts from PD patients display flawed nucleotide excision repair (NER) capacity and that Ercc1 mutant mice with mildly compromised NER exhibit typical PD-like pathological alterations, including decreased striatal dopaminergic innervation, increased phospho-synuclein levels, and defects in mitochondrial respiration. Ercc1 mouse mutants are also more sensitive to the prototypical PD toxin MPTP, and their transcriptomic landscape shares important similarities with that of PD patients. Our results demonstrate that specific defects in DNA repair impact the dopaminergic system and are associated with human PD pathology and might therefore constitute an age-related risk factor for PD. © 2016 The Author(s).